The Cost of Medically Unnecessary Days Due to Waiting for Guardianship in a State Acute Hospital System - Patricia Brierley-Bowers EdD, PMP; Heather Connors PhD; Joanne Tompkins PhD; Peter M. Macy EdM, JD (SAGE Publishing, 2022)
Hospitals must do more with less, making efficiency a priority. Discharge delays create challenges for acute care hospitals. Some delays are due to patients waiting for a guardian-a person appointed to assist an adult who lacks decision-making capacity. Previous studies examine the burden of excess days in a single academic medical center (AMC); however, these institutions do not represent the entire hospital system. This descriptive study expands upon previous analyses by calculating the financial implications of medically unnecessary days in a state's hospitals to payers. Two models are presented: one calculates the gross patient service revenues required to support excess days; the other calculates the expense to hospitals. Results suggest that substantial funds are required to support excess days. Funds may be better allocated to support the health and well-being of people needing medical care or to address the cause of delays due to waiting for guardianship.